Marketing digital para el incremento de las ventas del restaurante 3 hermanas, cantón Naranjal - Alvarado Acuria, Gabriela Roció (2024)
The 3 Hermanas Restaurant is an establishment dedicated to the sale of traditional and typical food, its owner is the Lady, Yadira Gorotiza, who founded it in 2012 and whose location is in the Naranjal canton of the province of Guayas, in front of the tourist inn. Currently, the 3 Hermanas Restaurant is in an economically tense situation, due to low sales and poor strategic management for proper functioning. As part of the objective of the research, it was proposed to develop digital marketing to increase sales of the 3 Hermanas restaurant in the Naranjal canton. Regarding the research methodology, the deductive method was applied, since it allowed us to evaluate that the effectiveness of digital marketing was a crucial factor for increasing sales of the 3 Hermanas Restaurant. Therefore, from a quantitative perspective, it was possible to verify the correlation that the application of digital marketing strategies has with the increase in sales of the 3 Hermanas Restaurant. Among the results obtained, it was evident that Tres Hermanas can obtain a significant boost in its sales through digital marketing. With an active audience on social networks such as Instagram, Facebook and TikTok, the creation of relevant and attractive content, such as images of dishes, special promotions and customer testimonials, could increase your visibility and attract new customers. In addition, customer service, speed of service and problem resolution can help strengthen the restaurant's reputation.